2000
DOI: 10.1023/a:1007576903935
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results indicate that another transporter(s) is involved in the hepatic uptake of indomethacin and the canalicular transport of indomethacin glucuronide is mediated by cMOAT/MRP2 whereas that of indomethacin is not mediated by cMOAT/MRP2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…The competitive inhibitory effect of IDM on the BSP transport also should be considered because Oatp1b2 and Mrp2 are also responsible for the biliary excretion of IDM and its glucuronide. 29,30) However, a pilot study showed that it seemed to be minor because a coadministration of IDM (1.0 mg/kg) at 2 h prior to BSP injection affected neither its plasma elimination nor biliary excretion (data not shown). The reduction in the mRNA levels of Oatp1b2 and Mrp2 was similar to that in their protein levels (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The competitive inhibitory effect of IDM on the BSP transport also should be considered because Oatp1b2 and Mrp2 are also responsible for the biliary excretion of IDM and its glucuronide. 29,30) However, a pilot study showed that it seemed to be minor because a coadministration of IDM (1.0 mg/kg) at 2 h prior to BSP injection affected neither its plasma elimination nor biliary excretion (data not shown). The reduction in the mRNA levels of Oatp1b2 and Mrp2 was similar to that in their protein levels (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of co-transfection with an expression construct for the Na ϩ -taurocholate co-transporting polypeptide was also determined. Na ϩ -taurocholate co-transporting polypeptide is found on the basolateral membrane of hepatocytes, and is the major protein responsible for transporting bile acids from the blood into the liver, and exhibits affinity for both conjugated and unconjugated bile acids (31,32). As shown in Fig.…”
Section: Cloning and Expression Of Murine Mrp3mentioning
confidence: 99%
“…A recent in vivo investigation of three drugs, considered MRP2 substrates by in vitro studies, found that EHBR mutant rats had negligible capacity for biliary export of two of the drugs, probenecid and methotrexate, but they had a comparable biliary output of the third, furosemide [18]. Dominant roles for MRP2 were demonstrated for biliary export of the glucuronide metabolites of the nonsteroidal anti-inflammatory drugs (NSAIDs), diclofenac and indomethacin, whereas minor or no apparent roles were found for the parent compounds of the NSAIDs indomethacin and sulindac [19][20][21]. Delays in the biliary output of glucuronide and sulfate metabolites of the type II diabetes drug trogliatazone were observed Consequences of MRP2 Deficiency 233 in TR À rats, which is consistent with transport by a compensatory lowaffinity biliary exporter, once metabolites have accumulated within hepatocytes [22].…”
Section: Influence Of Mrp2-deficiency On Biliary Export Of Endogenousmentioning
confidence: 99%
“…Based on observations in MRP2-deficient rats, biliary secretion of the acyl glucuronide metabolites of two NSAIDs, diclofenac and indomethacin, occurs predominantly via the MRP2 exporter. For indomethacin, a 2-fold decrease in its glucuronide metabolite was measured in bile collected following drug treatment of MRP2-deficient rats as compared with bile from wild-type rats [20]. For diclofenac, there appears to be a more dramatic impact as only trace levels of its glucuronide metabolites were recovered in bile of MRP2-deficient rats as compared with recovery of >50% of the dose administered in wild-type rats [21,38].…”
Section: Altered Responses Of Mrp2-deficient Rats To Nsaidsmentioning
confidence: 99%